Arctic Strategy of Japan and Russian National Interests - G. I. Gribanova; A. V. Magdalyuk (Евразийская интеграция: экономика, право, политика, 2022)
This work examines the main directions of the Japanese Arctic policy, its impact on the development of Russian-Japanese cooperation in the region.Aim. The study aims to analyze the formation of the Japanese Arctic strategy, to define promising areas and problems of Russian-Japanese relations.Tasks. The authors identify the main stages of the Japanese Arctic policy, determine the significance of the Northern Sea Route (NSR) for Tokyo, study the areas of Russian-Japanese cooperation, assess the problems and prospects of bilateral cooperation in the Arctic.Methods. Using the method of comparative analysis, content analysis, event analysis, we have identified areas that contribute to the strengthening of Russian-Japanese relations in the Arctic and factors that can weaken this cooperation.Results. The study shows that Japan seeks to be an active actor in the Arctic processes, since this region will play a significant role in the development of the Japanese economy through the energy supplies diversification. Japan’s key partner here is Russia, and they are implementing a major energy project — Arctic LNG-2. The modernization of the NSR’s infrastructure is another promising area for the development of Russian-Japanese relations. However, there are contradictions that may affect their cooperation — this is the differences in definition the NSR status and the international legal status of the Arctic.Conclusion. Despite Japan’s interest in using the NSR and participation in energy projects in the Russian Arctic, there are some issues that make it difficult to strengthen their Arctic cooperation. There are the problem of the Kuril Islands and the difference in determining the status of the Arctic region.